2015
DOI: 10.2147/btat.s62986
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry products in the prevention of urinary tract infections: examining the evidence

Abstract: Cranberry (Vaccinium macrocarpon) juice and extracts are widely used and recommended as folk remedy for prophylaxis of urinary tract infections (UTIs). Its putative mechanism is an anti-adhesive effect that prevents docking of bacteria on host tissues. The antiadhesion quality is attributed to A-type proanthocyanidins (PACs), a group of polyphenols that has a restricted occurrence in cranberries and a few related plants. Clinical trials with cranberry have provided a mixed evidence on behalf of UTI prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(94 reference statements)
0
3
0
1
Order By: Relevance
“…Specifically, one of the most studied procyanidin-based approaches for UTI treatment was the use of cranberry-based products (juice, powder, or nutraceuticals) due to their high title of PACs. The patients that potentially could benefit from cranberry prophylaxis include premenopausal women with frequent but mild UTIs, postmenopausal women with more severe recurrent UTIs, and children and adults with near-permanent and complicated genitourinary malformations with UTIs [ 43 ]. One of the first clinical trials that evaluated the efficacy of cranberry juice in the treatment of UTIs was performed by Avorn et.…”
Section: Proanthocyanidinsmentioning
confidence: 99%
“…Specifically, one of the most studied procyanidin-based approaches for UTI treatment was the use of cranberry-based products (juice, powder, or nutraceuticals) due to their high title of PACs. The patients that potentially could benefit from cranberry prophylaxis include premenopausal women with frequent but mild UTIs, postmenopausal women with more severe recurrent UTIs, and children and adults with near-permanent and complicated genitourinary malformations with UTIs [ 43 ]. One of the first clinical trials that evaluated the efficacy of cranberry juice in the treatment of UTIs was performed by Avorn et.…”
Section: Proanthocyanidinsmentioning
confidence: 99%
“…The AHPA Botanical Safety Handbook classifies cranberry as Safety Class I (i.e., an herb that can be safely consumed when used appropriately) [17]. One published review assessing cranberry in the prevention of UTIs reported that besides issues with palatability, there are no safety concerns [17,68]. Nevertheless, some potentially serious AEs have been reported in case reports describing the use of cranberry.…”
Section: First Authormentioning
confidence: 99%
“…Fresh, dried fruits and juice of Cranberries contain various components particularly flavonoids like flavonols myricetin and quercetin, which are considered a significant source of antioxidants and antiinflammatory Skrovankova [14]. Therefore, these substances act as a potent antioxidant, which could prevent and reduce infecting of the urinary tract, through its inhibitory effect on the bacterial activity that causes infections in the urinary tract Nowack [15].…”
Section: Cranberriesmentioning
confidence: 99%